Navigating Innovation and Cultural Diversity: The Role of Artificial Intelligence in Enhancing Arabic Language Learning Across Global Contexts - Azisi Azisi; Dwi Juli Priyono; Jinan Mohammed Al-Obaidi (Learning, Media and Technology in Arabic Education, 2025)
ABSTRACT  Background of study: As Arabic spreads across continents, its instruction is increasingly shaped by global mobility and digital transformation. Yet, disparities in access, shifting dialects, and fragmented educational approaches continue to hinder consistent learning outcomes. Aims and scope of paper: This paper explores how Arabic language education can benefit from the synergy of artificial intelligence and culturally aware teaching methods. It seeks to uncover the extent to which digital innovations can bridge gaps in pedagogy, accessibility, and learner engagement across diverse cultural settings. Methods: Using a qualitative descriptive lens, the research draws on in-depth interviews with Arabic language educators in varied regions, supported by a review of academic sources and policy documents. Through thematic analysis, the study captures the nuances of technological integration and intercultural teaching challenges. Result: The study found that AI tools—such as language recognition systems and adaptive learning platforms—contribute positively to Arabic instruction by offering interactive, personalized experiences. However, their effectiveness is uneven, limited by digital infrastructure gaps, lack of teacher readiness, and insufficient context-sensitive materials. Nevertheless, some approaches—like translanguaging and AI-generated feedback—are showing encouraging results in addressing learner diversity and inclusion. Conclusion: While technology alone cannot solve the complexities of teaching Arabic in multicultural contexts, its thoughtful use alongside culturally grounded pedagogy presents a path forward. To build more equitable language learning systems, educational reforms must emphasize localized resources, teacher training, and inclusive digital access.